Synthesis of DOTA-Based 43Sc Radiopharmaceuticals Using Cyclotron-Produced 43Sc as Exemplified by [43Sc]Sc-PSMA-617 for PSMA PET Imaging - Jason P. Meier; Mohammed Bhuiyan; Richard Freifelder; Hannah J. Zhang; Lucas Gonzalez; Antonino Pusateri; Hsiu-Ming Tsai; Lara Leoni; Kaustab Ghosh; Erica Markiewicz; Christopher Henning; Yuhan Zhang; et al. (Methods and Protocols, 2025)
The implementation of theranostics in oncologic nuclear medicine has exhibited immense potential in improving patient outcomes in prostate cancer with the implementation of [68Ga]Ga-PSMA-11 PET and [177Lu]Lu-PSMA-617 into clinical practice. However, the correlation between radiopharmaceutical biodistributions seen with [68Ga]Ga-PSMA-11 PET imaging and downstream [177Lu]Lu-PSMA-617 therapy remains imperfect. This suggests that prostate cancer theranostics could potentially be further refined through the implementation of true theranostics, tandem pairs of diagnostic and therapeutic radiopharmaceuticals that utilize the same ligand and element, thus yielding identical pharmacokinetics. The radioscandiums are one such group of true theranostic radiopharmaceuticals. The radioscandiums consist of two β+ emitting scandium isotopes (43Sc/44Sc), as well as a β− emitting therapeutic isotope (47Sc), which can all conjugate with PSMA-targeting PSMA-617. This potential has led to extensive investigations into the production of the radioscandiums as well as pre-clinical assessments with several ligands; however, there is a lack of literature extensively describing the complete synthesis of scandium radiopharmaceuticals. which therefore limits the accessibility of radioscandium research in theranostics. As such, this work aims to present an easily translatable protocol for the synthesis of [43Sc]Sc-PSMA-617 from a [42Ca]CaCO3 starting material, including target formation, nuclear production via 42Ca(d,n)43Sc reaction, chemical separation, radiolabeling, solvent reformulation, and target recycling.